QTc Interval Reference Values and Their (Non)-Maturational Factors in Neonates and Infants: A Systematic Review - Lisa De Smet; Nathalie Devolder; Thomas Salaets; Anne Smits; Karel Allegaert (MDPI AG, 2022)
QTc interval measurement is a widely used screening tool to assess the risk of cardiac diseases, arrhythmias, and is a useful biomarker for pharmacovigilance. However, the interpretation of QTc is difficult in neonates due to hemodynamic maturational changes and uncertainties on reference values. To describe trends in QTc values throughout infancy (1 year of life), and to explore the impact of (non)-maturational changes and medicines exposure, a structured systematic review (PROSPERO CRD42022302296) was performed. In term neonates, a decrease was observed over the first week of life, whereafter values increased until two months of age, followed by a progressive decrease until six months. A similar pattern with longer QTc values was observed in preterms. QTc is influenced by cord clamping, hemodynamic changes, therapeutic hypothermia, illnesses and sleep, not by sex. Cisapride, domperidone and doxapram result in QTc prolongation in neonates. Further research in this age category is needed to improve primary screening practices and QTcthresholds, earlier detection of risk factors and precision pharmacovigilance.